Malocclusion class III treatment in teething decidua. - Chávez Sevillano, Manuel Gustavo (2006)
According as age increases, growth decreases and Class III skeletal patterns become more stable. The objective of Class III malocclusion’s treatment in primary dentition is to get a favorable environment to achieve a better dentofacial development. This article’s objective is to give a theorical summary about treatment of Class III malocclusions in primary dentition, and to present a case report.